Guidance needs of lower and upper elementary students in Greater Beirut schools - Beydoun, Anisa Naji (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2014)
The design of School Guidance and Counseling Programs that are supposed to meet students needs have long been based on expert judgments. Some researchers suggested that including students' perceptions of their own needs serves in better design of School Guidance and Counseling Programs. Very limited research has been available worldwide on including self-reported needs of students in the intention to develop better counseling programs. Some Canadian studies (Drefs, 2002; Gordon, 2000; Kemeny, 1997; Robinson,1999) have used modified versions of Collins (1998) Student Needs Survey in order to identify the self-reported needs of students across all school levels. Some of these studies also compared between the perceptions of students and adults (parents and educators) about the needs of students. Other studies compared the differences of student self-reported needs across grade levels (Couture, 2002; Drefs, 2003) Knowing that in Lebanon there is a limited research on self-reported needs of students, especially in the lower elementary and upper elementary levels, this study aims to identify the needs of lower and upper elementary students in Greater Beirut public and private schools by including the perspective of students, parents, and school educators. Student Needs Surveys used in Drefs (2002) and Robinsons (1999) studies have been modified to suit the Lebanese context and translated to Arabic and used in this study. The needs assessed by the survey are clustered around three main areas: Service, Instruction, and Environment. The study was conducted in 9 schools in Greater Beirut (6 private, 3 public). The sample (N= 732 ) included 288 students, 382 parents, and 62 educators. Parents answered the survey at home and returned it with their children; all participating students - except Grade 1 and Grade 2 - answered the survey on their own in the classroom under the supervision of the investigator. The survey questions were read by the investigator to Grade 1 and Grade 2 students in small groups of 5-7. Educators filled the survey on their own at their convenience in the school. Results showed that all participants across elementary levels, and across private and public schools have reported high need for all the need subscales of the survey. Results showed that lower elementary students reported same level of need for both Environment and Instruction needs followed by Service needs. On the other hand, upper elementary students reported highest need for Environment, then Instruction followed by Service needs. The differences between both elementary levels were mainly in Environment and Service areas but not Instruction area. Lower elementary students agreed more with parents and less with educators, whereas upper elementary students agreed more with educators and less with parents.Public school students expressed more need than private school students on a wide range of needs. Conclusions of the study have been presented, limitations of the study have been considered, and implications for future research have been proposed.
: Mémoire
Keywords: Cycle primaire; Elementary Education; Grand Beirut; Grand Beyrouth; Orientation et Conseil; School guidance and counseling